The genomic bases of atrial fibrillation in an Ecuadorian patient: a case report - Tamayo-Trujillo, Rafael; Guevara-Ramirez, Patricia; Meza-Chico, Leonel; Cadena-Ullauri, Santiago; Ruiz-Pozo, Viviana A.; Paz-Cruz, Elius; Laso-Bayas, José Luis; Ibarra-Castillo, Rita; Zambrano, Ana Karina (Frontiers in Cardiovascular Medicine, 2025)
Atrial fibrillation (AF) is one of the most globally prevalent arrhythmias with multifactorial factors, including environmental and genetic predisposition influences. The present case report describes a 30-year-old Ecuadorian mestizo male diagnosed with persistent AF with an history of hyperthyroidism, later progressing to hypothyroidism post-radioactive iodine therapy. Genomic test identified variants of uncertain significance in the TTN, MYH11, and RAF1 genes, which are associated with cardiovascular diseases but not directly linked to AF. The interplay between thyrotoxicosis and genetic predispositions is discussed as a potential mechanism underlying AF development. This report emphasizes the need for genomic screening and personalized strategies in populations like Ecuador with complex genetic and environmental backgrounds.